CAN THE SHARIA SUPERVISORY BOARD (SSB) WEAKEN TAX AVOIDANCE ACTIVITIES BY ISLAMIC COMMERCIAL BANKS (ICB) IN INDONESIA? - Firmansyah, Amrie; Ihsan, Muhammad (Politeknik Keuangan Negara STAN, 2024)
This study examines the effect of leverage, fixed asset intensity, and profitability on tax avoidance with the number of Sharia Supervisory Board (SSB) as a moderating variable at Islamic Commercial Banks (ICB) in Indonesia. The sample for this research was 45 observations from ICBs that published annual reports from 2019 – 2023. The method used is panel data multiple linear regression analysis. The results showed that leverage has a negative effect on tax avoidance, while fixed asset intensity and profitability have a positive effect on ICB tax avoidance. Furthermore, the number of SSBs weakens the negative relationship between leverage and tax avoidance and weakens the positive relationship between fixed asset intensity and profitability on ICB tax avoidance. The results of this study have several recommendations. First, ICBs in Indonesia should adjust the number of their SSBs according to their tax planning by increasing or decreasing the number of SSBs. Larger SSB councils can increase supervision of the application of Sharia values and suppress tax avoidance practices, while smaller SSB councils give more room for management to plan the ICB tax. Second, the tax authority should collaborate with the Indonesian Financial Services Authority (OJK) to enforce good corporate governance relating to SSB to suppress tax avoidance activity in ICBs and ultimately optimize national revenues.